Ensuring quality of health workforce education and practice: strengthening roles of accreditation and regulatory systems - William Burdick; Ibadat Dhillon (BMC, 2020)
Abstract Regulation of the health workforce and accreditation of educational institutions are intended to protect the public interest, but evidence of the impact of these policies is scarce and occasionally contradictory. The body of research that does exist primarily focuses on policies in the global north and on the major health professions. Stress on accreditation and regulatory systems caused by surges in demand due to the COVID-19 pandemic, privatization of education, rising patient expectations, and emergence of new health worker categories has created urgency for innovation and reform. To understand and evaluate this innovation, we look forward to receiving manuscripts which contribute to the evidence base on the implementation, management, and impact of health worker education and practice regulation, including the intersection of education accreditation and workforce regulation policy. We particularly look forward to manuscripts from underrepresented parts of the globe and underrepresented health workforce sectors that address policy effectiveness, explore different models of regulation, and present innovations that we can all learn from.